Multilocus phylogeny, natural history traits and classification of natricine snakes (Serpentes: Natricinae). Issue 1 (30th November 2021) - Deepak, V; Cooper, Natalie; Poyarkov, Nikolay A; Kraus, Fred; Burin, Gustavo; Das, Abhijit; Narayanan, Surya; Streicher, Jeffrey W; Smith, Sarah-Jane; Gower, David J
Abstract: Natricine snakes are geographically widespread, species rich (with ~250 extant species) and both morphologically and ecologically diverse. We present a multilocus DNA sequence phylogeny for 249 natricine specimens representing 189 named species, including 69 specimens and 21 species not previously sampled. Our inferred Bayesian and maximum likelihood trees form the basis for evaluations of genus-level classification, historical biogeography, lineage diversification, and dietary, habit and reproductive-mode diversity and evolution, although several, mostly deeper, relationships remain poorly resolved. The optimal trees support natricine origins in Asia, with dispersals to Australo-Melanesia, sub-Saharan Africa (including Seychelles Archipelago, excluding Aldabra), Europe and North Africa and into North and Central America. Viviparity appears to have evolved independently three times in Natricinae but was not significantly associated with an aquatic habit. We found limited associations between habit and diet categories. We propose generic reallocations for four natricine species and highlight other points of uncertainty in natricine classification.